Perlindungan Hukum terhadap Harta Perkawinan dengan Pembuatan Akta Perjanjian Pra Nikah menurut Undang-Undang No. 1 Tahun 1974 - Yuvirani Sabrianti; Maman Sudirman; Benny Djaja (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the legal protection of marital assets through a prenuptial agreement under Law Number 1 of 1974 and to examine the implications of the Constitutional Court Decision Number 69/PUU-XIII/2015 on the validity of prenuptial agreements in Indonesia. Using a normative legal research method with statutory, conceptual, and case approaches, this study focuses on doctrinal analysis and juridical argumentation. The findings indicate that a prenuptial agreement functions as a preventive legal protection instrument that provides legal certainty, fairness, and utility for both husband and wife in regulating the ownership and management of assets. Such agreements serve as a “law” for the parties, protecting personal property, inherited assets, and financial arrangements during marriage. The Constitutional Court’s decision expanded the scope of time for drafting such agreements, which were previously limited to before marriage, and now may also be made during the marriage. The implication of this ruling reinforces the principle of freedom of contract, ensures greater legal flexibility, and enhances the relevance of prenuptial agreements in addressing contemporary social and economic dynamics. Therefore, a prenuptial agreement is not merely a legal formality but a strategic legal instrument that safeguards marital assets in Indonesia.